An investigation into the effects of the pricing policy on financial performance of public sector entities: a case study of the Judicial Service Commission - Madzivire, Jackford (Midlands State University, 2017)
For the period 2011 to 2013, the Commission has been poorly performing financially. The expenditure has always been more than the revenue. The poor performance has been seen to be as a result of the pricing system adopted by the Commission. This research focused on an investigation into the effects of pricing system on financial performance in public sector entities, taking a case study of the Judicial Service Commission. The study made use of the descriptive research design, where interviews were conducted and self administered questionnaires were distributed as the main data collection methods. Related historic literature was also incorporated so as to make references and also guide the investigation. Four interviews were conducted out of a target of six, with members of staff of the Commission, and also twenty questionnaires were distributed, obtaining a response of fifteen. Data obtained were both qualitative and quantitative, hence was presented and analysed using charts, tables and graphs. The study indicated through the findings that the Commission has powers to set prices for its services. Irrespective of this, the JSC goes without a pricing policy guide, and this has resulted in prices being far below the marginal cost of offering the service. The pricing system currently used fall outside the commonly known pricing systems in the public sector. The Commission also does not have a review procedure manual, neither does it exercise price reviews unless there are extenuating circumstances that forces it to do so, like currency changes or inflation. This has caused the Commission to use prices that were pegged more five years. This in itself led to poor financial performance for the Commission throughout the period under review, 2011 to 2013. Major recommendations were that the Commission urgently need to craft a pricing procedure manual that do not permit setting of price structures that falls below the marginal cost. The pricing procedure manual also has to address the review exercise and the period within which the exercise has to be undertaken. The JSC also should adopt the commonly, tried and tested pricing strategies, for which the break even pricing or the marginal cost pricing strategies are recommended.